Citrus bioflavonoid, hesperetin, as inhibitor of two thrombin-like snake venom serine proteases isolated from Crotalus simus. (1st March 2018) - Vander dos Santos, Roney; Villalta-Romero, Fabian; Stanisic, Danijela; Borro, Luiz; Neshich, Goran; Tasic, Ljubica
Abstract: Around 5.5 million people suffer from snakebites per year, with about 400, 000 cases with some type of sequelae, such as amputation, and 20, 000 to 125, 000 cases with the fatal end. Usually, the victim outcome depends on correct, agile and many times in situ intervention based on the proper identification of the snake venom type and its potential effects, among other factors. Therefore, knowledge on the snake venom composition and a research on inhibitors of snake venom target components might ameliorate envenoming dangerous outcome. Herein, two thrombin-like serine proteases from the Crotalus simus snake venom - SVSP1 and SVSP2 - were isolated in two chromatographic steps, using gel filtration and then RP-HPLC. They showed molecular masses of around 31.3 and 24.6 kDa, respectively, and mostly β-sheet secondary structure features. The SVSP1 and SVSP2 were sequenced using tandem mass spectrometry (Q-TOF). Using the known serine protease structure (PDB entry:4e7n ), which was evaluated as homologous to the two target proteins, in silico docking results showed that hesperetin is its excellent inhibitor. Using in vitro tests with the commercial hesperetin, kinetic parameters were obtained for SVSPs against the synthetic substrate BA p NA. Obtained results pointed that hesperetin might act as an uncompetitive (SVSP1) or mixed (SVSP2) inhibitor. Also, the fluorescence quenching upon inhibition was observed, as well as, red shift in maximums of around 20 nm, which indicate that the tryptophan residues in the target enzymes suffered conformational changes caused by hesperetin binding. Thus, a naturally occurring flavone that can easily be extracted from oranges might serve as low-cost inhibitor of the investigated snake venom proteases. Graphical abstract: Highlights: Two thrombin-like snake venom serine proteases were isolated from the Crotalus simus and physico-chemically characterized. Citrus bioflavonoid, hesperetin showed to be a promising inhibitor of two snake venom proteases. In silico and in vitro experiments point to hesperetin as a mixed or non-competitive inhibitor. Hesperetin topical application might ameliorate envenoming effects.